Molecular Pathology of Sodium Channel Beta-Subunit Variants - Angsutararux, Paweorn; Zhu, Wandi; Voelker, Taylor L.; Silva, Jonathan R. (Frontiers in Pharmacology, 2021)
The voltage-gated Na+ channel regulates the initiation and propagation of the action potential in excitable cells. The major cardiac isoform NaV1.5, encoded by SCN5A, comprises a monomer with four homologous repeats (I-IV) that each contain a voltage sensing domain (VSD) and pore domain. In native myocytes, NaV1.5 forms a macromolecular complex with NaVβ subunits and other regulatory proteins within the myocyte membrane to maintain normal cardiac function. Disturbance of the NaV complex may manifest as deadly cardiac arrhythmias. Although SCN5A has long been identified as a gene associated with familial atrial fibrillation (AF) and Brugada Syndrome (BrS), other genetic contributors remain poorly understood. Emerging evidence suggests that mutations in the non-covalently interacting NaVβ1 and NaVβ3 are linked to both AF and BrS. Here, we investigated the molecular pathologies of 8 variants in NaVβ1 and NaVβ3. Our results reveal that NaVβ1 and NaVβ3 variants contribute to AF and BrS disease phenotypes by modulating both NaV1.5 expression and gating properties. Most AF-linked variants in the NaVβ1 subunit do not alter the gating kinetics of the sodium channel, but rather modify the channel expression. In contrast, AF-related NaVβ3 variants directly affect channel gating, altering voltage-dependent activation and the time course of recovery from inactivation via the modulation of VSD activation.